PENGEMBANGAN MEDIA PEMBELAJARAN FEATURE VIDEO BERBASIS ADOBE PREMIERE PRO PADA TEMA 1 ORGAN GERAK HEWAN DAN MANUSIA SUBTEMA MANUSIA DAN LINGKUNGAN PEMBELAJARAN 4 KELAS V SEKOLAH DASAR - Liana Parhana; Ana Nurhasanah; Ratna Sari Dewi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is focused on the developmental and feasibility process and students’ responses to Adobe Premier Pro-based feature video learning media. The method used was Research and Development (R&D) with the ADDIE development model (analysis, design, development, implementation, and evaluation). The sample involved the fifth-grade students who were selected by using the purposive sampling technique. Methods of data collection were questionnaires, observation, and documentation. Determination of the feasibility level of video feature-based learning media was tested by expert validation and tried out to students through questionnaires. The results showed that the level of feasibility based on the test conducted by material experts was 91.4% with 14 assessment aspects, media experts were 95.7% with 14 assessment aspects, linguists were 93.3% with 9 assessment aspects, and the student’s response for the first question was 82.35%, the second question was 85.29%, the third question was 100%, the third question of -4 was 91.18%, the fifth question was 82.35%, and the sixth question was 100%. Based on the expert test and trial assessments, the development of feature video learning media based on Adobe Premiere Pro on the theme of animal and human movement organs class V at SD Negeri Sanding 2 was very feasible to be used as a learning medium